2016
DOI: 10.1007/s00264-016-3302-4
|View full text |Cite
|
Sign up to set email alerts
|

Different synovial vasculogenic profiles of primary, rapidly destructive and osteonecrosis-induced hip osteoarthritis. An immunohistochemistry study

Abstract: The severity of hip OA can be related to angiogenesis pathways that are not maspin-mediated. In primary hip OA, angiogenesis may be induced by a combined mechanism: hypoxia-related VEGF-dependent vasculogenesis and endothelial differentiation of the activated pluripotent cells, which are released from the hyperplastic synovial cells layer. An endothelial mesenchymal transition is assumed to be involved in the fibrotic process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that VEGF can promote vascular proliferation, enhance vascular permeability and that VEGF levels are closely related to the progression of RA (Gurzu et al, 2017). In the present study, low levels of VEGF expression was found in the synovium of Control rats, suggesting that this factor plays a role in maintaining the normal function of the synovium.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that VEGF can promote vascular proliferation, enhance vascular permeability and that VEGF levels are closely related to the progression of RA (Gurzu et al, 2017). In the present study, low levels of VEGF expression was found in the synovium of Control rats, suggesting that this factor plays a role in maintaining the normal function of the synovium.…”
Section: Discussionmentioning
confidence: 99%
“…The approbative effects of bioactive glasses implants are not limited to osseous regeneration, as it was shown that they induce an increased vascularity in bone lesions of earlier irradiated calvaria [16]. Bioactive Glass seems to be a very good solution for treating osteomyelitis, traumatic pseudarthrosis, revision prosthesis interventions or other pathologies involving bone tissue resorbtion or bone defects [18, [25][26][27][28][29]. This scaffold seems to be a proper substitute for other treatment in hip revision arthroplasty [23,24].…”
Section: Resultsmentioning
confidence: 99%
“…from the vascularised synovium and that there was an invasion of synovium into the articular cartilage [ 43 ]. Furthermore, in a study investigating the role of angiogenesis in hip OA, it was noted that the grade of angiogenesis was related to the cartilage degeneration, hence it could be involved in the degenerative process [ 44 ].…”
Section: Discussionmentioning
confidence: 99%